The art of Harry Potter - Sumerak, Marc (New York Harper Design, 2017)
"This book presents a visual chronicle of the work by the artists and filmmakers of all eight Harry Potter films who made the magic real."--Front jacket flap.
Keywords: Harry Potter and the sorcerer's stone (Motion picture) -- Pictorial works; Harry Potter and the Chamber of Secrets (Motion picture) -- Pictorial works; Harry Potter and the prisoner of Azkaban (Motion picture) -- Pictorial works; Harry Potter and the Half-Blood Prince (Motion picture) -- Pictorial works; Harry Potter and the Order of the Phoenix (Motion picture) -- Pictorial works; Harry Potter and the Deathly Hallows, part 1 (Motion picture) -- Pictorial works; Harry Potter and the Deathly Hallows, part 2 (Motion picture) -- Pictorial works; Harry Potter and the goblet of fire (Motion picture) -- Pictorial works; Motion pictures -- Production and direction